Legal Protection Reform for Children Conflicted with Law - Emy Rosna Wati (Rechtsidee, 2014)
The government has long been giving protection to children. Protection is reflected in the issuance of various Law. One of them is the Law No. 23 of 2003 on Child Protection. The legal protection of children in conflicted with law and child as victims of crime are regulatedin articlenumber 64. Issuance of Law No. 3 of 1997 on Juvenile Court actually originates from a passion for protecting the rights of children in conflicted with the law. However, due to inadequate understanding and mindset of Juvenile Court, which is do not have the children’s perspective, what comes up is that the substance of Law on Juvenile Court is not to protect children but to prosecute children. However, after the release of Law No. 11 of 2012 onThe Criminal Justice System of Children, legal protection of children in conflict with the law was encouragingly reformed. How To Cite: Rosna Wati, E. (2014). Legal Protection Reform for Children Conflicted with Law. Rechtsidee, 1(1), 59-70. doi:http://dx.doi.org/10.21070/jihr.v1i1.101